Molecular and cytological detection of BK polyoma virus in kidney failure patients - Saeed, Ibrahim Mohammed; Ali, Hajar (Iraqi Journal of Science, 2025)
These days, the kidney transplant community widely agrees that BK virus infections are the main driver behind kidney impairment and transplant failures. A total of 110 kidney failure patients were enrolled in this study. Five ml of blood was collected from each patient, the plasma was separated, and then the plasma samples were stored until DNA extraction was performed. Molecular detection of BK was done by polymerase chain reaction (PCR). Urine samples were also obtained for cytological detection and investigation of decoy cell. The results of the PCR technique for the current study revealed that 12 patients were infected with the BK polyoma virus at a prevalence rate of 10.9 %, with 8 infections in males and 4 infections in females, with a rate of 12.5% and 8.7% respectively. The results of cytological testing and electron microscopy also demonstrated that all 8 urine samples taken from patients infected with the virus contained decoy cells and virus particles. we conclude that chronic hemodialysis could raise the chance of BK virus replication in end stage renal dialysis patients as compared to control group. It was also concluded that chronic hemodialysis may increase the likelihood of BK virus replication in patients with end-stage renal disease compared to the control group.